Equity audit: challenges and basic verification procedures - Барышева, С.; Турлыбекова, A. (Journal of Economic Research & Business Administration, 2017)
The article about audit of equity, which includes checking of timeliness and legitimacy of its formation, compliance with its value changing order and accurancy of reflections of operations in accounting. Equity capital is aggregate of assets and funds, investments and costs for the acquisition of rights and privileges necessary for the performance of its business activities. The financial statements of the organization must impartially and fairly present financial position of the organization, results of operations, cash flows and changes in shareholders’ equity and changes in the organization’s own capital. Equity audit begins with a study of the data of the report on changes in shareholders’ equity in the formation of the equity capital, as well as the expression of an opinion on these accounting and financial statements indicators’ reliability, reflecting the state of the equity.